2010
DOI: 10.1177/0956797610377342
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Congruity Between Goals and Roles

Abstract: Although women have nearly attained equality with men in several formerly male-dominated fields, they remain underrepresented in the fields of science, technology, engineering, and mathematics (STEM). We argue that one important reason for this discrepancy is that STEM careers are perceived as less likely than careers in other fields to fulfill communal goals (e.g., working with or helping other people). Such perceptions might disproportionately affect women's career decisions, because women tend to endorse co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
347
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 657 publications
(414 citation statements)
references
References 14 publications
15
347
2
2
Order By: Relevance
“…Beyond the control variables, the key predictor variables that addressed questions (2) and (3) in the regression were the sustainability topic items. The outcome variables were science agency (2) and physics identity (3). Throughout this analysis, the maximum allowed chance of Type I error, was fixed at 5%.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the control variables, the key predictor variables that addressed questions (2) and (3) in the regression were the sustainability topic items. The outcome variables were science agency (2) and physics identity (3). Throughout this analysis, the maximum allowed chance of Type I error, was fixed at 5%.…”
Section: Data Collection and Methodsmentioning
confidence: 99%
“…Much of recent science education research has focused on empowering students in their science learning by increasing their level of input as well as crossing boundaries from the world of the classroom to a more relevant social and physical world outside the classroom [3]. We believe that this is an important direction for physics education though it may be more difficult in physics than the other sciences since the physics curriculum is driven by a traditional canon of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that physical/mathematical sciences are seen as being less able to afford goals that involve other people [9]. Students may think instead of the "lone scientist" or "technology and machinery" [10]. Finally, individuals have been found to align their interests and aspirations to those that coincide with the roles that society has ascribed for them [10].…”
Section: Outcome Expectationsmentioning
confidence: 99%
“…Students may think instead of the "lone scientist" or "technology and machinery" [10]. Finally, individuals have been found to align their interests and aspirations to those that coincide with the roles that society has ascribed for them [10]. For example, women maintain high association levels with communal roles (caring for other people) and physics is not perceived as communal such that "even scientifically talented women frequently choose other careers" [10].…”
Section: Outcome Expectationsmentioning
confidence: 99%
“…We focus on two challenges. First, we highlight efforts to leverage values of "helping others" and "giving back to one's community"-values women frequently cite as absent from STEM professions (Diekman, Brown, Johnston, & Clark, 2010;Intel Corporation, 2014;Konrad, Ritchie, Lieb, & Corrigall, 2000)by encouraging a personal relationship between builders and clients. Second, we discuss design choices made to assist workshop participants as they manage transitions between phases of the design process.…”
Section: Volume 8 Issue 1 | Pages 1-10mentioning
confidence: 99%